The Ambivalence of the Internet and Technology upon the Comic Industry - Emha, Adhani Juniasyaroh (Department of Communications, Universitas Islam Indonesia, 2024)
The advent of the internet and technology has brought ambivalence to the comic industry. On one hand, they provide consumers and comic enthusiasts with easy access to their favorite comics without needing to visit bookstores. On the other hand, they have exacerbated the issue of piracy. This paper is based on a qualitative comparative study, comparing two types of official and illegal comic publications on internet platforms, including Webtoon, CIAYO, Mangareader, Mangafox, and Bato. This paper outlines the distribution process of legal printed and digital comics and reveals how comic piracy is perpetrated and proliferated, particularly on internet-based platforms. This study shows that the ambivalence of technological development is inevitable in the comic culture industry. Piracy in the world of comics is inevitable. Illegal groups assume that translations, re-uploads and the like will make it easier for readers to understand comics, but they are still illegal. On the other hand, legal comics have also taken various measures to minimize piracy. Comic industries, especially those that operate online, have implemented measures to protect their authors’ works from piracy. For instance, Webtoon, a platform created by Naver, has disabled the screenshot function on readers’ devices, preventing them from capturing images of comics that could be misused.